Representing teacher coaching sessions: understanding coaching that develops teachers' capability to design for learning - Kickbusch, Steven; Kelly, Nick (International journal of mentoring and coaching in education, 2021)
PurposeThe purpose of this paper is to develop representations for teacher coaching sessions that are (1) useful for communicating the session to other coaches or researchers and (2) capture the roles of the coach as convener of dialogue for teacher development as well as facilitator of design for learning.Design/methodology/approachTwo coaching sessions with preservice science teachers are analysed using two forms of discourse analysis: (1) the T-SEDA coding scheme (Vrikki et al., 2019) to analyse the dialogic interaction; and (2) a novel coding scheme to show the development of the design for learning over time. A synthetic representation is developed that combines and communicates the results of both analyses.FindingsResults show a novel way of representing coaching sessions with teachers during design for learning. Theoretical claims about the utility of this representation are made with reference to the literature.Practical implicationsThe representations and methods for developing them are useful to researchers in analysing coaching sessions. They have application for helping coaches to communicate their practice with one another. They are a step towards understanding the scalability and transferability of coaching programmes for school improvement.Originality/valueThe paper highlights shortcomings of existing representations for teacher coaching sessions and produces a novel representation that has value for researchers.